"Are You Into Beer Pong?" Exploring Question-Answer Sequences in an L2 Oral Performance Assessment. Issue 1 (1st January 2019) - Timpe-Laughlin, Veronika; Park, Innhwa
ABSTRACT: Despite the frequent occurrence of yes/no questions in naturalistic talk-in-interaction, there is widespread concern that yes/no questions only allow predetermined answers and limit L2 learners' performance in language assessment contexts. Drawing upon audio-recordings of role-play conversations between an L1 American English speaker and 104 L2 English learners, we use conversation analysis to examine how L2 learners respond to yes/no questions in an oral performance assessment. The analysis was guided by the following research questions: (a) How do L2 English learners respond to a yes/no interrogative in a role-play assessment context? (b) How do L2 English learners' different responses lead to distinct sequences of conversational turns? In our analysis we show that yes/no interrogatives elicit a range of responses (e.g., repair initiation, type-conforming responses, non-type-conforming responses) that result in negotiation of meaning between participants. While turn design and sequence organization features we observed largely align with the existing literature on naturally occurring conversations, we also discuss deviant cases that provide insights into L2 learner discourse. Moreover, we discuss the findings in terms of implications for L2 assessment.